The Effect of Using E-Learning Based Guided Discovery Learning Model Based on Self-Efficacy Towards Student Learning Outcomes In Biology Class in Reproductive System Subject in High School - Atiyah, Umu; Miarsyah, Mieke; Sigit, Diana Vivanti (International Journal for Educational and Vocational Studies, 2020)
Guided Discovery Learning is a learning model that is considered capable of improving student learning outcomes while Self-efficacy is self-confidence in an individual’s abilities. This study aims to determine the effect of guided discovery learning model and self-efficacy towards student learning outcomes in biology class. The method used in this research is quasi-experimental. This study has a sample of 200 students from 256 students. The technique used is Cluster random sampling. The instruments used are multiple choices and questionnaire. Data from the three variables are analysed using the Two-Way ANOVA Test and the Tukey Test, at a significance level of 0.005. Based on data analysis, it can be concluded that Guided Discovery Learning model and an individual’s self-efficacy can improve student learning outcomes. Both Guided Discovery Learning model and self-efficacy can improve student learning outcomes and have positive interactions between the two variables. The implications of this study are as a basis for increasing the use of learning models using technology, and teachers as educators are able to encourage students to improve self-efficacy.